Triage and Prioritize Procedures in Oral and Maxillofacial Surgery during COVID-19 Pandemic and a Review of Literature - Dehghanpour Baruoj, Mehrdad; Khojasteh, Arash (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: The novel coronavirus disease (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus, is rapidly expanding. Due to the rapid spread of this disease through respiratory droplets, oral and maxillofacial surgery can be correlated with a high risk of Covid 19 transmission. Materials and Methods: A comprehensive review of the literature has been done for this purpose. Interventions were prioritized based on their necessity and urgency for the well-being of the patients. Results: Although Elective surgery must be delayed until COVID-19 pandemic situation has been insolvent, urgent surgery can be done in negative pressure operative room on the patients with Covid 19 and with the adequate personal equipment protection in healthy patients. Conclusion: Triage and prioritize of procedures in oral and maxillofacial surgery during Covid 19 pandemic is of great importance.